Aerobic exercise attenuates high-fat diet–induced renal injury through kidney metabolite modulation in mice - Yingzhe Xiong; Yisheng Luan; Lingfeng Yuan; Weihao Hong; Bin Wang; Hua Zhao; Bing Zhang (Renal Failure)
Purpose To investigate the preventive effect of aerobic exercise on renal damage caused by obesity.Methods The mice in the Control (Con) and Control + Exercise (Con + Ex) groups received a standard chow diet for the 21-week duration of the study, while the High-fat diet (HFD) group and High-fat diet + Exercise (HFD + Ex) group were fed an HFD. Mice were acclimated to the laboratory for 1 week, given 12 weeks of being on their respective diets, and then the Con + Ex and HFD + Ex groups were subjected to moderate intensity aerobic treadmill running 45 min/day, 5 days/week for 8 weeks.Results We found that HFD-induced obesity mainly impacts kidney glycerin phospholipids, glycerides, and fatty acyls, and aerobic exercise mainly impacts kidney glycerides, amino acids and organic acids as well as their derivatives. We identified 18 metabolites with significantly altered levels that appear to be involved in aerobic exercise mediated prevention of HFD-induced obesity and renal damage, half of which were amino acids and organic acids and their derivatives.Conclusion Aerobic exercise rewires kidney metabolites to reduce high-fat diet-induced obesity and renal injury.